EXPERIMENTAL STUDY OF LIGHTWEIGHT CONCRETE MECHANICAL QUANTITY WITH HEATED STYROFOAM MATERIAL - Lukman, Wiwik; Sumirin, Sumirin; Antonius, Antonius (AGUSPATI Research Institute, 2021)
Research on lightweight concrete based on styrofoam aggregates has been carried out previously, namely by providing heat treatment to styrofoam before being used as a substitute for aggregate with fine grains. The Styrofoam used is Expanded Polystyrene (EPS) with a grain size of 5 – 8 mm before being heated. Styrofoam seeds were heated at a temperature of 1380 C for 7 minutes. The variation of the test object in this study was using styrofoam as a substitute for 100% coarse aggregate and 75% coarse aggregate replacement so that the remaining 25% coarse aggregate used gravel with sizes of 10x10 mm and 10x20 mm. To close the pores of the concrete in this variation of the test object, 30 % of the weight of the aggregate was also added with fly ash. To improve the workability, a superplasticizer of 0.6% of the cement weight was used.The tests carried out are compressive strength, split tensile strength and flexural strength. The results obtained were the optimum value of the compressive strength test of 19.57 MPa on lightweight concrete with heavy coarse aggregate replaced by 100% heated styrofoam. For the optimum value of the split tensile strength test, it was found that 2.83 MPa in lightweight concrete, the weight of coarse aggregate was replaced by 75% styrofoam and 25% gravel with a size of 10x20 mm. For the optimum value of the flexural strength test, it was obtained at 3.27 MPa in lightweight concrete, the weight of coarse aggregate was replaced by 75% styrofoam and 25% gravel with a size of 10x10 mm.